Sensory experiences and cues among E-cigarette users - J. DiPiazza; P. Caponnetto; G. Askin; P. Christos; M. Lyc Psych Maglia; R. Gautam; S. Roche; R. Polosa (BMC, 2020)
Abstract Background and aims We characterized the extent and quality of respiratory sensations and sensory-related smoking cues associated with e-cigarette use among those who failed to quit combustible tobacco cigarette (CTC) use with traditional FDA approved medications but succeeded in doing so with e-cigarettes. Further, we sought to understand former smokers' perceptions about the influence of sensory experience with e-cigarette use on CTC cessation outcomes. Methods A nonrandom purposive sample of 156 participants recruited in the USA through the Consumer Advocates for Smoke Free Alternatives Association Facebook page completed an online cross-sectional survey to assess sensory experiences and smoking cues associated with e-cigarette use. Descriptive statistics were calculated, and the ANOVA/Kruskal-Wallis test with post hoc testing and the two-sample t test/Wilcoxon rank-sum test, as appropriate based on distribution, were used to assess the association between sample characteristics and sensory experiences and cues using investigator constructed questions, the Modified Cigarette Evaluation Questionnaire (mCEQ) and the Smoking Cue Appeal Survey (SCAS). Results With e-cigarette use, participants reported feeling the vapor in their throats, windpipes, noses, lungs, and on their tongues; reductions in nicotine craving; and enjoyment of their e-cigarette, including tasting, smelling, and seeing the vapor and touching the device. Women had greater craving reduction than men (p = 0.023). Those who began smoking at 13 years of age or younger had more satisfaction and had greater sensory enjoyment than those who began smoking at 16-17 years of age (p = 0.015 and p = 0.026, respectively), as well as greater sensory enjoyment than those who began smoking at 14-15 years of age (p = 0.047). There was a significant overall association between the number of years a respondent smoked and e-cigarette sensory enjoyment (p = 0.038). Participants 18-34 years old rated e-cigarettes as being more pleasant compared to 45 + years olds, (p = 0.012). Eighty-four percent of participants reported the sensation of the vapor as important in quitting CTCs, and 91% believed the sensations accompanying e-cigarette use contributed to their smoking cessation success. Conclusions For those who failed to quit previously using approved cessation medications to stop smoking cigarettes, sensory experiences associated with e-cigarette use may help smokers quit smoking.